Properties characterization and microstructural analysis of alkali-activated solid waste-based materials with sawdust and wastewater integration. - Liang Li; Xianhui Zhao; Haoyu Wang; Jianran Cao; Xian-En Zhao (PLoS ONE)
Construction materials are significantly exposed to ecological hazards due to the presence of hazardous chemical constituents found in industrial and agricultural solid wastes. This study aims to investigate the use of sawdust particles (SDPs) and sawdust wastewater (SDW) in alkali-activated composites (AACs) made from a mixture of different silicon-aluminum-based solid wastes (slag powder-SP, red mud-RM, fly ash-FA, and carbide slag-CS). The study examines the impact of SDP content, treated duration of SDPs, and SDW content on both fresh and hardened properties of the AACs, including electrical conductivity, fluidity, density, flexural and compressive strengths, and drying shrinkage. The study also analyzes the microstructures and product compositions of the AACs influenced by SDW through a comprehensive analysis of microstructures and product compositions by using XRD, SEM-EDS, and FTIR. The results show that treating SDPs with a 2.5 mol/L NaOH solution for 12 hours decreases the fluidity and electrical conductivity of the AACs but improves their flexural and compressive strengths. Additionally, in the synthesis of a composite material incorporating binder materials SP, RM, and FA in a mass ratio of 10:3:18, a 2.0 mol/L NaOH solution is employed. The liquid-to-solid ratio is maintained at 20:31, and the sand-to-binder ratio is set at 3:1. The substitution of 12.28% SDW to NaOH solution improves the resistance to drying shrinkage and long-term mechanical strength development of the AACs. Interestingly, the addition of SDW does not affect the product compositions due to the generation and decomposition of organic acid salts from organic impurities in the acidic SDW during long-term curing at room temperature. These findings provide valuable insights for the sustainable recycling of bioresources and solid wastes containing silicon-aluminum in construction materials.